Pyrolytic Behavior of Long-Chain Alkyl Quaternary Ammonium Bromide Inside Nanopores - Niu, Yanhui; Yu, Wenbin; Yang, Shuguang; Wan, Quan (Frontiers in Energy Research, 2021)
The pyrolytic behavior of organic matter inside nanopores was studied by simultaneous thermogravimetric/differential scanning calorimetry analyzer coupled with Fourier transform infrared spectroscopy (STA/TG-FTIR). Nanoporous silica was prepared by a hydrothermal method using long-chain alkyl quaternary ammonium bromide (CnTAB, n = 12, 14) as a template. The pyrolytic behavior of CnTAB inside nanopores with different diameters was investigated and compared with that of CnTAB inside and outside nanopores. The results showed that the pyrolytic removal process consisted of the following features: 1) CnTAB underwent carbon chain decomposition and oxidation; 2) the DSC exothermal peak of CnTAB came mainly from its oxidative combustion, and the oxidative combustion temperature decreased with increasing pore size; 3) the CnTAB inside nanopores underwent crystallization–amorphous state phase transition, and CnTAB got trapped inside the calcined nanopores. In addition, the pyrolytic behavior of CnTAB inside the calcined nanopores was found to be similar to that of the uncalcined nanopores. This study aims to understand the storage and transformation processes of organic hydrocarbons under nanopore-confinement effect.